2019
DOI: 10.1086/704887
|View full text |Cite
|
Sign up to set email alerts
|

Arctic biodiversity of stream macroinvertebrates declines in response to latitudinal change in the abiotic template

Abstract: We aimed to determine which processes drive patterns of a and b diversity in Arctic river benthic macrofauna across a broad latitudinal gradient spanning the low to high Arctic of eastern Canada (58 to 81 o N). Further, we examined whether latitudinal differences in taxonomic composition resulted from species replacement with organisms better adapted to northerly conditions or from the loss of taxa unable to tolerate the harsh environments of higher latitudes. We used the bioclimatic envelope concept to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…For example, geographical location determines the species pool from which local communities are assembled, and thus local communities show imprints of both regional and local factors [421,432]. Recent studies have also shown that biological communities in northern freshwater ecosystems are clearly affected by climate over broad areas, as has been observed for algae [433], macroinvertebrates [434], and fish [419]. Finally, land use, land cover, and catchment heterogeneity have been found to be associated with both alpha and beta diversity variation of macrophytes (e.g., [435]) and macroinvertebrates (e.g., [428]).…”
Section: Boreal and Arctic Freshwater Habitatsmentioning
confidence: 94%
“…For example, geographical location determines the species pool from which local communities are assembled, and thus local communities show imprints of both regional and local factors [421,432]. Recent studies have also shown that biological communities in northern freshwater ecosystems are clearly affected by climate over broad areas, as has been observed for algae [433], macroinvertebrates [434], and fish [419]. Finally, land use, land cover, and catchment heterogeneity have been found to be associated with both alpha and beta diversity variation of macrophytes (e.g., [435]) and macroinvertebrates (e.g., [428]).…”
Section: Boreal and Arctic Freshwater Habitatsmentioning
confidence: 94%
“…Interannual and seasonal variability, as well as the timing of the sampling period, plays a large role in determining the abundance of benthic invertebrates collected using biomonitoring approaches (Hawkins et al., 2010). Depending on yearly precipitation and heat, the abundance of assemblages can vary greatly since there is a clear relationship between variability of macroinvertebrate α diversity and air temperature variation (Culp et al., 2019); this is especially true in Arctic environments where seasonality is known to have significant control over invertebrate abundances (Danks, 2007). Indeed, for Arctic environments, there is an expectation that the natural temporal variability of invertebrates is high (Meyer et al., 2017) and could be based on stochastic factors (Miller & Stout, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Water samples were sent to the National Laboratory for Environmental Testing (Burlington, Ontario, Canada) for analysis using standardized methods (Environment Canada 2017). The variables were chosen to represent established physical and ecological gradients in the Mackenzie Delta (Lesack et al 1998;Squires et al 2009;Tank et al 2011) and include variables that have been found to structure BMI communities in Arctic regions (e.g., Culp et al 2019) and (or) deltaic floodplain lakes (e.g., Gallardo et al 2008).…”
Section: Collection Methodsmentioning
confidence: 99%